Preparation process of ultra-clean high-purity acetic acid
By adsorbing organic impurities in the acetic acid preparation process by modified cellulose and nitrogen, sulfur and molybdenum doped carbon adsorbents, the problem of inability to effectively remove metal ions, dust particles and organic impurities in the prior art is solved, and high purity is achieved The preparation of acetic acid improves product quality and process efficiency.
Patent Information
- Application Number
- CN202411286592.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
AI Technical Summary
The existing acetic acid preparation process cannot effectively remove metal ions, dust particles and organic impurities, especially moisture and easily azeotropic organic impurities, and cannot meet the production needs of high-purity acetic acid, affecting the performance of electronic-grade components.
Adsorption filtration is performed by modified cellulose and nitrogen, sulfur and molybdenum doped carbon adsorbents, combined with crude distillation and rectification processes, control moisture content and temperature, and doped carbon by modified cellulose and nitrogen, sulfur and molybdenum. Adsorbent adsorbs and removes organic impurities in acetic acid.
It significantly improves the purity of acetic acid, reduces the content of metal ions, moisture and organic impurities, improves product quality, simplifies the process flow, reduces energy consumption, and is suitable for industrial production.
Smart Images

Figure BDA0005043265180000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic-grade chemical preparation, and specifically relates to a preparation process of ultra-clean high-purity acetic acid. Background Art
[0002] Electronic grade acetic acid is one of the wet electronic chemicals used in the microelectronics industry. It can be used to clean silicon wafers, effectively remove impurity particles, inorganic residues and carbon deposits on the wafers, and is widely used in the production of photovoltaic solar cells, flat panel displays, integrated circuits and other electronic components.
[0003] During the production, transportation and storage of acetic acid, due to raw materials and equipment reasons, some metal ions, dust particles, unreacted raw materials and intermediate products are inevitably introduced into the product, and these impurities can easily lead to the generation of staggered layers, resulting in PN combined leakage current, breakdown, etc. For integrated circuits with smaller line widths, in addition to very few metal ions and particles that may destroy the entire circuit, organic matter in the solvent, such as aldehydes (strongly reducible), etc., also affect the performance of the circuit. Therefore, with the rapid development of integrated circuits, the requirements for the purity of electronic-grade reagents are getting higher and higher. How to effectively remove metal ions, dust particles and organic impurities is a technical problem that needs to be solved urgently. For acetic acid, since its impurities such as 2-butenal and 2-ethyl-2-butenal easily form azeotropes with water, how to efficiently remove moisture and organic impurities is also a topic that needs to be overcome urgently.
[0004] CN114989005A discloses a method for preparing electronic-grade acetic acid, which comprises the following steps: step 1: removing part of the metal ions in the initial industrial-grade acetic acid by using ion exchange resin; step 2: further rectifying the acetic acid obtained in step 1; step 3: purifying and filtering the rectified acetic acid again by using ion exchange resin to obtain the electronic-grade acetic acid. The process is simple, but the removal effect of water and metal ions cannot meet the requirements of high-purity acetic acid, and does not involve the removal of azeotropic organic impurities.
[0005] DE602007056379T2 discloses a method for purifying acetic acid, wherein an acetic acid product stream and a hydroxy compound selected from the group consisting of 2-methyl-1,3-propanediol, 1,3-propanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-dimethyl-1,3-propanediol, cyclohexane-1,4-dimethanol and a mixture thereof are fed into a distillation column, wherein aldehyde impurities react with the hydroxy compound to form acetal, wherein water is removed from the top of the distillation column and a substantially water-free acetic acid product stream containing acetic acid and acetal is taken out from the distillation column. This patent provides a new method for removing aldehydes, but the removal efficiency is low.
[0006] In the existing disclosed preparation process, the removal efficiency of impure metals, particles, organic impurities and moisture is low, which cannot meet the production of high-grade electronic-grade acetic acid and the needs of large-scale production. Summary of the invention
[0007] The invention provides a preparation process of ultra-clean high-purity acetic acid, aiming to provide a new and efficient method to reduce the content of impurities such as metals, particles, water and the like in electronic-grade acetic acid and improve the quality of acetic acid.
[0008] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a process for preparing ultra-clean high-purity acetic acid. To achieve the above technical objectives, the technical solution adopted by the present invention is: a process for preparing ultra-clean high-purity acetic acid, comprising the following steps:
[0009] (1) Rough distillation: using industrial acetic acid as raw material, the moisture content is controlled to be less than or equal to 3% after rough distillation;
[0010] (2) Adsorption: The temperature of the crudely distilled acetic acid is controlled at 40-50°C, and adsorption filtration is performed using modified cellulose and nitrogen, sulfur, and molybdenum doped carbon adsorbents;
[0011] (3) Distillation: The adsorbed acetic acid is distilled to collect the fractions;
[0012] (4) cooling the fraction and filtering it to obtain ultra-clean high-purity acetic acid;
[0013] The preparation steps of the modified cellulose include: modifying carboxylated cellulose with tetraethylenepentamine to obtain modified cellulose;
[0014] The preparation steps of the nitrogen, sulfur and molybdenum doped carbon adsorbent are: nitrogen source, molybdenum source, sulfur source and activated carbon form a dispersion liquid, and the dispersion liquid is placed in a closed environment for hydrothermal reaction.
[0015] Preferably, the mixing ratio of the modified cellulose and the nitrogen, sulfur, and molybdenum doped carbon adsorbent is 1:4-4:1.
[0016] More preferably, the filtration is performed using an electronic grade filter.
[0017] Preferably, the temperature of the hydrothermal reaction is 190-210°C.
[0018] Preferably, the molybdenum source is at least one of ammonium heptamolybdate and ammonium molybdate.
[0019] Preferably, the sulfur source is at least one of thiourea, thioacetamide and ammonium sulfide.
[0020] Preferably, the hydrothermal reaction temperature is 200°C.
[0021] Preferably, the nitrogen source is at least one of urea and triethylamine.
[0022] Preferably, the activated carbon is activated carbon that has been activated.
[0023] Preferably, the average length of cellulose is 800 nm or less.
[0024] Preferably, the average aspect ratio of cellulose is 300 or less.
[0025] Optionally, the distillation conditions are: the number of tower plates is greater than or equal to 45, the top pressure is 0.21-0.3 MPa, the top temperature is 120-128°C, the bottom pressure is 0.29-0.36 MPa, the bottom temperature is 142-147°C, and the reflux ratio is 4-10.
[0026] Preferably, the activated carbon is activated by impregnation with hydrogen peroxide for 2-6 hours, followed by filtration and drying. After activation and modification, the number of oxygen-containing functional groups such as hydroxyl, carboxyl, and ester groups on the surface of the activated carbon increases significantly.
[0027] Preferably, the activated activated carbon is added to a mixed solution containing a molybdenum source, a sulfur source, and a nitrogen source, stirred for 12-24 hours, and the mixture is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, heated at 190-210°C for 12-24 hours, and naturally cooled to room temperature; after filtering, it is washed alternately with deionized water and ethanol for at least three times, and then dried.
[0028] Preferably, the steps of grafting tetraethylenepentamine on carboxylated cellulose are: dispersing carboxylated cellulose in deionized water, adding N-hydroxysuccinimide and EDC, stirring at room temperature, adding primary amine, adjusting the pH to 3-6, reacting at 50-70°C for 6-12h, then adding tetraethylenepentamine, maintaining the pH at 3-6, reacting at room temperature for 24-48h, separating and drying to obtain modified carboxylated cellulose; preferably, the primary amine is n-hexylamine or n-nonylamine.
[0029] The present invention adopts a modified adsorbent for adsorption after crude distillation. The adsorbent has good adsorption properties for organic impurities in acetic acid, such as acetaldehyde, 2-butenal, 2-ethyl-2-butenal, etc., especially for the adsorption of 2-butenal and 2-ethyl-2-butenal, and can solve the problem that distillation cannot effectively remove some organic impurities.
[0030] Another aspect of the present invention is the use of modified carboxylated cellulose prepared by the above method and nitrogen, sulfur, and molybdenum doped carbon adsorbent in removing 2-butenal and 2-ethyl-2-butenal from acetic acid solvent.
[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects.
[0032] (1) The process flow and equipment used in the present invention have high yield and stable product quality, are convenient for industrial production, and are highly practical. The number of distillation steps is reduced, energy consumption is reduced, and the separation process is simple, without causing additional environmental pollution.
[0033] (2) The present invention uses specific modified cellulose and nitrogen, sulfur, and molybdenum doped carbon adsorbents for adsorption, which can effectively remove organic impurities in acetic acid and avoid the problem that organic-water azeotropes cannot be separated by distillation. DETAILED DESCRIPTION
[0034] The following embodiments are merely examples covered by the present invention and do not constitute any limitation to the scope of implementation.
[0035] Example 1
[0036] A purification process for ultra-clean high-purity acetic acid, specifically, firstly, crude distillation is performed on industrial-grade acetic acid with a concentration of 70%, and a fraction at 118-119°C is collected, and the moisture content is controlled to be less than 1%. The fraction is cooled to 50°C and supplied to an adsorption column filled with modified carboxylated cellulose and nitrogen, sulfur, and molybdenum doped carbon adsorbents. The adsorbed acetic acid liquid enters a distillation device, and the distillation conditions are: 60 plates, 0.21MPa tower top pressure, 120°C tower top temperature, 0.29MPa tower bottom pressure, 142°C tower bottom temperature, and 4 reflux ratio. After the acetic acid flows out from the top of the tower, it is filtered through an electronic grade filter to obtain ultra-clean high-purity acetic acid.
[0037] Preparation method of nitrogen, sulfur and molybdenum doped carbon adsorbent: the first step is to impregnate activated carbon with hydrogen peroxide for 4 hours, the concentration of hydrogen peroxide is 30%, and then filter and dry after impregnation, and the drying condition is 105℃ for 6 hours to obtain activated activated carbon. The second step is to add the activated activated carbon to a mixed dispersion containing ammonium molybdate, thiourea and urea, and the mass ratio of activated carbon, ammonium molybdate, thiourea and urea is 6:2:3.6:1, stir for 24 hours, transfer the mixture to a stainless steel autoclave lined with polytetrafluoroethylene, heat at 200℃ for 24 hours, and cool naturally to room temperature; after filtering, wash alternately with deionized water and ethanol for at least three times, and then dry to obtain nitrogen, sulfur and molybdenum doped carbon adsorbent.
[0038] The steps of tetraethylenepentamine modified carboxylated cellulose are as follows: dispersing carboxylated cellulose in deionized water, adding N-hydroxysuccinimide and EDC, stirring at room temperature, adding n-hexylamine, reacting at 70°C for 6 hours, then adding tetraethylenepentamine, reacting at room temperature for 48 hours, separating and drying to obtain modified carboxylated cellulose, wherein the mass ratio of cellulose, N-hydroxysuccinimide and EDC, n-hexylamine, and tetraethylenepentamine is 100:100:6:24. The average length of cellulose is 700nm, and the average aspect ratio is 160.
[0039] The mixing ratio of nitrogen, sulfur, and molybdenum doped carbon adsorbent and tetraethylenepentamine modified carboxylated cellulose is 1:1.
[0040] Example 2
[0041] A purification process for ultra-clean high-purity acetic acid, specifically, firstly, crude distillation is performed on industrial-grade acetic acid with a concentration of 70%, and a fraction at 118-119°C is collected, and the moisture content is controlled to be less than 1%. The fraction is cooled to 50°C and supplied to an adsorption column filled with modified carboxylated cellulose and nitrogen, sulfur, and molybdenum doped carbon adsorbents. The adsorbed acetic acid liquid enters a distillation device, and the distillation conditions are: 60 plates, 0.21MPa tower top pressure, 120°C tower top temperature, 0.29MPa tower bottom pressure, 142°C tower bottom temperature, and 4 reflux ratio. After the acetic acid flows out from the top of the tower, it is filtered through an electronic grade filter to obtain ultra-clean high-purity acetic acid.
[0042] Preparation method of nitrogen, sulfur and molybdenum doped carbon adsorbent: the first step is to impregnate activated carbon with hydrogen peroxide for 4 hours, the concentration of hydrogen peroxide is 30%, and then filter and dry after impregnation, and the drying condition is 105℃ for 6 hours to obtain activated activated carbon. The second step is to add the activated activated carbon to a mixed dispersion containing ammonium molybdate, thiourea and urea, and the mass ratio of activated carbon, ammonium molybdate, thiourea and urea is 6:2:3.6:1, stir for 24 hours, transfer the mixture to a stainless steel autoclave lined with polytetrafluoroethylene, heat at 200℃ for 24 hours, and cool naturally to room temperature; after filtering, wash alternately with deionized water and ethanol for at least three times, and then dry to obtain nitrogen, sulfur and molybdenum doped carbon adsorbent.
[0043] The steps of tetraethylenepentamine modified carboxylated cellulose are as follows: dispersing carboxylated cellulose in deionized water, adding N-hydroxysuccinimide and EDC, stirring at room temperature, adding n-hexylamine, reacting at 70°C for 6 hours, then adding tetraethylenepentamine, reacting at room temperature for 48 hours, separating and drying to obtain modified carboxylated cellulose, wherein the mass ratio of cellulose, N-hydroxysuccinimide and EDC, n-hexylamine, and tetraethylenepentamine is 100:100:6:24. The average length of cellulose is 700nm, and the average aspect ratio is 160.
[0044] The mixing ratio of nitrogen, sulfur, and molybdenum doped carbon adsorbent and tetraethylenepentamine modified carboxylated cellulose is 1:4.
[0045] Example 3
[0046] A purification process for ultra-clean high-purity acetic acid, specifically, firstly, crude distillation is performed on industrial-grade acetic acid with a concentration of 70%, and a fraction at 118-119°C is collected, and the moisture content is controlled to be less than 1%. The fraction is cooled to 50°C and supplied to an adsorption column filled with modified carboxylated cellulose and nitrogen, sulfur, and molybdenum doped carbon adsorbents. The adsorbed acetic acid liquid enters a distillation device, and the distillation conditions are: 60 plates, 0.21MPa tower top pressure, 120°C tower top temperature, 0.29MPa tower bottom pressure, 142°C tower bottom temperature, and 4 reflux ratio. After the acetic acid flows out from the top of the tower, it is filtered through an electronic grade filter to obtain ultra-clean high-purity acetic acid.
[0047] Preparation method of nitrogen, sulfur and molybdenum doped carbon adsorbent: the first step is to impregnate activated carbon with hydrogen peroxide for 4 hours, the concentration of hydrogen peroxide is 30%, and then filter and dry after impregnation, and the drying condition is 105℃ for 6 hours to obtain activated activated carbon. The second step is to add the activated activated carbon to a mixed dispersion containing ammonium molybdate, thiourea and urea, and the mass ratio of activated carbon, ammonium molybdate, thiourea and urea is 6:2:3.6:1, stir for 24 hours, transfer the mixture to a stainless steel autoclave lined with polytetrafluoroethylene, heat at 200℃ for 24 hours, and cool naturally to room temperature; after filtering, wash alternately with deionized water and ethanol for at least three times, and then dry to obtain nitrogen, sulfur and molybdenum doped carbon adsorbent.
[0048] The steps of tetraethylenepentamine modified carboxylated cellulose are as follows: dispersing carboxylated cellulose in deionized water, adding N-hydroxysuccinimide and EDC, stirring at room temperature, adding n-hexylamine, reacting at 70°C for 6 hours, then adding tetraethylenepentamine, reacting at room temperature for 48 hours, separating and drying to obtain modified carboxylated cellulose, wherein the mass ratio of cellulose, N-hydroxysuccinimide and EDC, n-hexylamine, and tetraethylenepentamine is 100:100:6:24. The average length of cellulose is 700nm, and the average aspect ratio is 160.
[0049] The mixing ratio of nitrogen, sulfur, and molybdenum doped carbon adsorbent and tetraethylenepentamine modified carboxylated cellulose is 4:1.
[0050] Comparative Example 1
[0051] A purification process for ultra-clean high-purity acetic acid, specifically, firstly, crude distillation is performed on industrial-grade acetic acid with a concentration of 70%, and a fraction at 118-119°C is collected, and the moisture content is controlled to be less than 1%. The fraction is cooled to 50°C and supplied to an adsorption column filled with modified carboxylated cellulose. The adsorbed acetic acid liquid enters a distillation device, and the distillation conditions are: 60 plates, a tower top pressure of 0.21MPa, a tower top temperature of 120°C, a tower bottom pressure of 0.29MPa, a tower bottom temperature of 142°C, and a reflux ratio of 4. After the acetic acid flows out from the top of the tower, it is filtered through an electronic grade filter to obtain ultra-clean high-purity acetic acid.
[0052] The steps of tetraethylenepentamine modified carboxylated cellulose are as follows: dispersing carboxylated cellulose in deionized water, adding N-hydroxysuccinimide and EDC, stirring at room temperature, adding n-hexylamine, reacting at 70°C for 6 hours, then adding tetraethylenepentamine, reacting at room temperature for 48 hours, separating and drying to obtain modified carboxylated cellulose, wherein the mass ratio of cellulose, N-hydroxysuccinimide and EDC, n-hexylamine, and tetraethylenepentamine is 100:100:6:24. The average length of cellulose is 700nm, and the average aspect ratio is 160.
[0053] Comparative Example 2
[0054] A purification process for ultra-clean high-purity acetic acid, specifically, firstly, crude distillation is performed on industrial-grade acetic acid with a concentration of 70%, and a fraction of 118-119°C is collected, and the moisture content is controlled to be less than 1%. The fraction is cooled to 50°C and supplied to an adsorption column filled with nitrogen, sulfur, and molybdenum-doped carbon adsorbent. The adsorbed acetic acid liquid enters a distillation device, and the distillation conditions are: 60 plates, a tower top pressure of 0.21MPa, a tower top temperature of 120°C, a tower bottom pressure of 0.29MPa, a tower bottom temperature of 142 degrees Celsius, and a reflux ratio of 4. After the acetic acid flows out from the top of the tower, it is filtered through an electronic grade filter to obtain ultra-clean high-purity acetic acid.
[0055] Preparation method of nitrogen, sulfur and molybdenum doped carbon adsorbent: the first step is to impregnate activated carbon with hydrogen peroxide for 4 hours, the concentration of hydrogen peroxide is 30%, and then filter and dry after impregnation, and the drying condition is 105℃ for 6 hours to obtain activated activated carbon. The second step is to add the activated activated carbon to a mixed dispersion containing ammonium molybdate, thiourea and urea, and the mass ratio of activated carbon, ammonium molybdate, thiourea and urea is 6:2:3.6:1, stir for 24 hours, transfer the mixture to a stainless steel autoclave lined with polytetrafluoroethylene, heat at 200℃ for 24 hours, and cool naturally to room temperature; after filtering, wash alternately with deionized water and ethanol for at least three times, and then dry to obtain nitrogen, sulfur and molybdenum doped carbon adsorbent.
[0056] Comparative Example 3
[0057] A purification process for ultra-clean high-purity acetic acid, specifically, firstly, crude distillation is performed on industrial-grade acetic acid with a concentration of 70%, and a fraction at 118-119°C is collected, and the moisture content is controlled to be less than 1%. The fraction is cooled to 50°C and supplied to an adsorption column filled with modified carboxylated cellulose and sulfur- and molybdenum-doped carbon adsorbents. The adsorbed acetic acid liquid enters a distillation device, and the distillation conditions are: 60 plates, 0.21MPa tower top pressure, 120°C tower top temperature, 0.29MPa tower bottom pressure, 142°C tower bottom temperature, and reflux ratio of 4. After the acetic acid flows out from the top of the tower, it is filtered through an electronic grade filter to obtain ultra-clean high-purity acetic acid.
[0058] Preparation method of sulfur- and molybdenum-doped carbon adsorbent: Step 1: impregnate activated carbon with hydrogen peroxide for 4 hours at a hydrogen peroxide concentration of 30%, filter and dry after impregnation at 105°C for 6 hours to obtain activated activated carbon. Step 2: add the activated activated carbon to a mixed dispersion containing ammonium molybdate and thiourea at a mass ratio of 6:2:3.6, stir for 24 hours, transfer the mixture to a stainless steel autoclave lined with polytetrafluoroethylene, heat at 200°C for 24 hours, and cool naturally to room temperature; after filtering, wash alternately with deionized water and ethanol for at least three times, and then dry to obtain sulfur- and molybdenum-doped carbon adsorbent.
[0059] The steps of tetraethylenepentamine modified carboxylated cellulose are as follows: dispersing carboxylated cellulose in deionized water, adding N-hydroxysuccinimide and EDC, stirring at room temperature, adding n-hexylamine, reacting at 70°C for 6 hours, then adding tetraethylenepentamine, reacting at room temperature for 48 hours, separating and drying to obtain modified carboxylated cellulose, wherein the mass ratio of cellulose, N-hydroxysuccinimide and EDC, n-hexylamine, and tetraethylenepentamine is 100:100:6:24. The average length of cellulose is 700nm, and the average aspect ratio is 160.
[0060] The mixing ratio of sulfur and molybdenum doped carbon adsorbent and tetraethylenepentamine modified carboxylated cellulose is 1:1.
[0061] Determination method:
[0062] Method for determining the mass fraction of acetic acid: an automatic titrator is used for the test. The specific method is to accurately weigh 1g of sample and add purified water to a 250ml volumetric flask, transfer 10ml of test solution-70ml of water, and titrate to the endpoint with a standard sodium hydroxide solution on the titrator, and perform a blank test at the same time.
[0063] Determination of metal ion mass fraction: Determined by inductively coupled plasma mass spectrometry (ICP-MS). Weigh 5g of sample to an accuracy of 0.01g, slowly put it into a 50mL volumetric flask containing a small amount of ultrapure water, cool to room temperature, dilute to scale with water, and shake well. Determine the signal intensity of each element in the sample under the same analytical conditions as the standard solution series, and perform a blank test at the same time. Determine the mass fraction of aluminum, arsenic, barium, boron, cadmium, calcium, chromium, cobalt, copper, gold, iron, lead, lithium, magnesium, manganese, nickel, potassium, silver, sodium, thallium, tin, titanium, vanadium, zinc, platinum, and antimony.
[0064] Particle size determination: The particle size was determined using a laser liquid particle counter.
[0065] The total concentration of organic impurities such as acetaldehyde, 2-butenal and 2-ethyl-2-butenal was quantitatively determined by GC-MS analysis (gas chromatography mass spectrometry).
[0066] See Table 1 for specific test data:
[0067]
[0068] The above embodiments and test data are only some applications and implementations of the present invention, and cannot limit the protection scope of the present invention. Through the above description, any technician in the relevant technical field can see that the present invention is innovated by adopting novel ideas and means, and has obvious practicality and creativity.
Claims
1. A process for preparing ultra-clean high-purity acetic acid, comprising the following steps: (1) Rough distillation: using industrial acetic acid as raw material, the moisture content is controlled to be less than or equal to 3% after rough distillation; (2) Adsorption: The temperature of the crudely distilled acetic acid is controlled at 40-50°C, and adsorption filtration is performed using modified cellulose and nitrogen, sulfur, and molybdenum doped carbon adsorbents; (3) Distillation: The adsorbed acetic acid is distilled to collect the fractions; (4) cooling the fraction and filtering it to obtain ultra-clean high-purity acetic acid; The preparation steps of modified cellulose include: Carboxylated cellulose is modified by using tetraethylenepentamine to obtain modified cellulose; The preparation steps of the nitrogen, sulfur and molybdenum doped carbon adsorbent are: nitrogen source, molybdenum source, sulfur source and activated carbon form a dispersion liquid, and the dispersion liquid is placed in a closed environment for hydrothermal reaction.
2. The process according to claim 1, characterized in that: The filtration is performed using an electronic grade filter.
3. The process according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 190-210°C.
4. The process according to claim 1, characterized in that: The molybdenum source is at least one of ammonium heptamolybdate and ammonium molybdate.
5. The process according to claim 1, characterized in that: The sulfur source is at least one of thiourea, thioacetamide and ammonium sulfide.
6. The process according to claim 3, characterized in that: The hydrothermal reaction temperature is 200°C.
7. The process according to claim 1, characterized in that: The nitrogen source is at least one of urea and triethylamine.
8. The process according to claim 1, characterized in that: The activated carbon is activated carbon that has been activated.
9. The process according to claim 1, characterized in that: The average length of the cellulose is 800 nm or less.
10. The process according to claim 1, characterized in that: The average aspect ratio of the cellulose is 300 or less.